2021
DOI: 10.1093/eurheartj/ehab593
|View full text |Cite
|
Sign up to set email alerts
|

Systematic, early rhythm control strategy for atrial fibrillation in patients with or without symptoms: the EAST-AFNET 4 trial

Abstract: Aims Clinical practice guidelines restrict rhythm control therapy to patients with symptomatic atrial fibrillation (AF). The EAST-AFNET 4 trial demonstrated that early, systematic rhythm control improves clinical outcomes compared to symptom-directed rhythm control. Methods and results This prespecified EAST-AFNET 4 analysis compared the effect of early rhythm control therapy in asymptomatic patients (EHRA score I) to symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 27 publications
(31 reference statements)
4
64
0
2
Order By: Relevance
“…Although these results may be confusing, they underscore the role that multimorbidity may affect the outcomes of rhythm control manage. Recent a prespecified EAST-AFNET 4 analysis compared the effect of early rhythm control therapy in asymptomatic patients (EHRA score I) to symptomatic patients, showed no difference in effectiveness of rhythm control strategy among symptomatic and asymptomatic patients, support the systematic, early initiation of rhythm control therapy in all patients with AF and concomitant cardiovascular conditions in dependent of their AF-related symptoms (27). Another prespecified sub-analysis of the randomized EAST-AFNET4 trial, find out rhythm control therapy conveys clinical benefit when initiated within 1 year of diagnosing AF in patients with signs or symptoms of HF (28).…”
Section: Discussionmentioning
confidence: 98%
“…Although these results may be confusing, they underscore the role that multimorbidity may affect the outcomes of rhythm control manage. Recent a prespecified EAST-AFNET 4 analysis compared the effect of early rhythm control therapy in asymptomatic patients (EHRA score I) to symptomatic patients, showed no difference in effectiveness of rhythm control strategy among symptomatic and asymptomatic patients, support the systematic, early initiation of rhythm control therapy in all patients with AF and concomitant cardiovascular conditions in dependent of their AF-related symptoms (27). Another prespecified sub-analysis of the randomized EAST-AFNET4 trial, find out rhythm control therapy conveys clinical benefit when initiated within 1 year of diagnosing AF in patients with signs or symptoms of HF (28).…”
Section: Discussionmentioning
confidence: 98%
“… 21) A similar proportion has been observed in other trials and registries, such as the AFFIRM trial and Global Anticoagulant Registry in the FIELD-Atrial Fibrillation (GARFIELD-AF) and Outcomes Registry for Better Informed Treatment of Atrial Fibrillation (ORBIT-AF) registries. 15) 61) 62) Recently, Willems et al 63) showed that the benefit of early rhythm control was consistently observed regardless of symptom status in the participants of the EAST-AFNET.…”
Section: Optimal Patient Selection For Early Rhythm Controlmentioning
confidence: 99%
“…Die internationalen Leitlinien empfehlen die Einleitung der rhythmuserhaltenden Therapie bei Patienten, die trotz adäquater Herzfrequenzkontrolle weiterhin symptomatisch sind. Eine Subanalyse der EAST-Studie konnte demonstrieren, dass asymptomatische Patienten mit einem EHRA-Stadium-I und kürzlich diagnostiziertem VHF von der Rhythmuskontrolle und damit vom Erhalt des Sinusrhythmus genauso profitieren wie symptomatische Patienten 32 ( Abb. 1 ).…”
Section: Symptomatisches Versus Asymptomatisches Vorhofflimmernunclassified
“…Subanalyse der EAST-AFNET-4-Studie unter Einbeziehung der symptomatischen und asymptomatischen Patienten. Der klinische Benefit eines prognostischen Vorteils der frühen Rhythmuskontrolle findet sich unabhängig von der Symptomatik bei symptomatischen und asymptomatischen Patienten im Vergleich zur Frequenzkontrolle (nach Daten aus[32]). EAST -AFNET 4 StudiePrimärer Endpunkt: kardiovaskulärer Tod, Schlaganfall oder Hospitalisierung aufgrund einer Verschlechterung der Herzinsuffizienz oder…”
unclassified